2010
DOI: 10.1002/14651858.cd001487.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Graft type for femoro-popliteal bypass surgery

Abstract: Analysis 2.1. Comparison 2 Above-knee PTFE versus all other graft materials, Outcome 1 Primary patency at 3 months. Analysis 2.2. Comparison 2 Above-knee PTFE versus all other graft materials, Outcome 2 Primary patency at 6 months. Analysis 2.3. Comparison 2 Above-knee PTFE versus all other graft materials, Outcome 3 Primary patency at 12 months. Analysis 2.4. Comparison 2 Above-knee PTFE versus all other graft materials, Outcome 4 Primary patency at 24 months. Analysis 2.5. Comparison 2 Above-knee PTFE versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 50 publications
0
77
0
5
Order By: Relevance
“…Some specifi ed procedures have been agreed being primarily suitable for surgical repair: • Complex lesion and coexisting severe renal failure, which may cause irreversible renal failure, if high amount of contrast agent is needed for endovascular intervention Autologous vein grafts provide best patency results and should be used whenever available [39] (LoR A).…”
Section: Critical Limb Ischaemiamentioning
confidence: 99%
“…Some specifi ed procedures have been agreed being primarily suitable for surgical repair: • Complex lesion and coexisting severe renal failure, which may cause irreversible renal failure, if high amount of contrast agent is needed for endovascular intervention Autologous vein grafts provide best patency results and should be used whenever available [39] (LoR A).…”
Section: Critical Limb Ischaemiamentioning
confidence: 99%
“…12, 13 The primary patency rate of bypass surgery was significantly higher than that for EVT, especially when autologous vein graft was used, while some studies have reported increased duration of hospitalization and some cases of wound infection after bypass surgery. 14, 15 There was a clear primary patency benefit for use of autologous vein as compared to synthetic materials for above-knee bypass. 16 Furthermore, avoidance of dual antiplatelet drugs is more advantageous in patients who have undergone bypass surgery than in those receiving stent placement with respect to preventing future bleeding.…”
Section: Outcome Of Evt Vs Bypassmentioning
confidence: 99%
“…Some studies stated that the primary patency rate of bypass surgery was considerably higher than endovascular treatment in femoropopliteal arterial diseases [12,13]. The endovascular treatment can be the first choice in the case of poor condition [14].…”
Section: Discussionmentioning
confidence: 99%